2018
DOI: 10.1080/09637486.2018.1492524
|View full text |Cite
|
Sign up to set email alerts
|

Higher vegetable protein consumption, assessed by an isoenergetic macronutrient exchange model, is associated with a lower presence of overweight and obesity in the web-based Food4me European study

Abstract: The objective was to evaluate differences in macronutrient intake and to investigate the possible association between consumption of vegetable protein and the risk of overweight/obesity, within the Food4Me randomised, online intervention. Differences in macronutrient consumption among the participating countries grouped by EU Regions (Western Europe, British Isles, Eastern Europe and Southern Europe) were assessed. Relation of protein intake, within isoenergetic exchange patterns, from vegetable or animal sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 68 publications
1
9
0
1
Order By: Relevance
“…The association is in contrary to diets high in animal protein. 38 The findings are also in accordance with observational studies and meta-analyses, which have described an association between a relatively low BMI and low-fat, high-carbohydrate diets, 10 including plant-based diets. 40 Plant-based diets are usually low in fats, particularly saturated fats, 40 as a natural consequence of the elimination of animal products.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The association is in contrary to diets high in animal protein. 38 The findings are also in accordance with observational studies and meta-analyses, which have described an association between a relatively low BMI and low-fat, high-carbohydrate diets, 10 including plant-based diets. 40 Plant-based diets are usually low in fats, particularly saturated fats, 40 as a natural consequence of the elimination of animal products.…”
Section: Discussionsupporting
confidence: 88%
“… 38 Nonetheless, BMI is a helpful and frequently used measure on weight and weight alterations in larger populations. 38 , 39 Of note, a recent study reporting on effects of ad-libitum consumed low-fat plant-based diets supplemented with plant-based meal replacements on body composition, reported that low-fat plant based-diets eaten ad libitum enabled significant reduction of body fat and relative preservation of muscle mass. 18 This suggests that a plant-based diet pose beneficial changes to body composition that might not be visible only by a BMI measure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In favor of whether plant-based diets benefit obese patients, Navas-Carretero and colleagues exploited the Food4Me study [ 36 ]. This study included 2413 European adult participants who completed online surveys of morphological data, dietary intake, and medical comorbidities at multiple time points during a 6 month intervention of personalized nutrition [ 37 ]. Comparing the population using a 25 kg/m 2 BMI cut-off, authors revealed subjects with the highest BMI had the highest animal protein consumption and the less vegetable protein one; moreover, substituting 1% of animal protein by vegetable protein reduced the risk of becoming overweight or obese.…”
Section: Using Proteins To Treat Obesitymentioning
confidence: 99%
“…In the last few years many studies started to questioning the effects of animal (e.g., meat and dairy products) and plant (e.g., grains and legumes) proteins intake on risk to develop cardiovascular disease and cancer [112,113]. In a recent meta-analysis proteins intake from plants is associated with a decrease risk of diabetes, whereas animal proteins with an increase of it [114,115].…”
Section: High Protein Diet In Nafld Cure or Disease?mentioning
confidence: 99%